Comovement of International Stock Market from the perspective of a nonparametric approach - Othman Yong (Penerbit Universiti Kebangsaan Malaysia, 1992)
Most of the past studies regarding the comovement of the international stock markets deal with the potential gains to investors from international portfolio diversification. In general, these studies suggested that considerable gains were available to investors who diversify internationally due to the usually low positive or negative correlations between national stock markets. This study, on the other hand, looks at this issue from the perspective of a nonparametric approach as apposed to the commonly used parametric approach in the past studies, due to the problem of nonnormality with data under study. This study uses weekly indices of the markets of the Malaysia, Hong Kong, Australia, Japan, the United Kingdom, and the United States for a period from January 1984 to December 1988. The results of this study indicate that the comovements among these markets are not stable with time, which means that it is difficult to construct an optimal investment strategy based on comovements of these markets.